(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2001)
Used motor oil reprocessing is offered also for Latvian conditions. The benefits from it consists in preventing of environment pollution by metal oxides and unknown toxic substances in flue gases, evolving from, or due to possible catalytic synthesis during the waste oil incineration, if the latter was disposed as before. The main such pollutants from Latvian waste oils are sulphur dioxide, Zn, P, Pb, Cr, Ni and Mo oxides, as well believed to be also heavy aromatic hydrocarbons. Besides, the reprocessing completely lifts up the subsoil water pollution danger in case o f waste oil occasional spillage.The used motor oil reprocessing by its recovery, vacuum distillation and marketing is proved to be economically profitable, if the world crude oil prices are not lower than 25 USD/bbl, and may serve as an additional resource for a local lube oil manufacturing for Latvia, as well as a way of diminishing of fresh lube oil imports.The main obstacles for the enterprise under consideration to be overcomed are believed to be the psychological inertia of oil users to dispose their wastes in a proper way and also the insufficient oil collection infrastructure in the country.